SAVINGS PATTERN OF COOPERATIVE THRIFT AND CREDIT SOCIETY MEMBERS IN IJEBU-NORTH LOCAL GOVERNMENT AREA OF OGUN-STATE, NIGERIA - Idowu, A. O.; Adetola, O. D.; Badejo, A. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study investigated savings patterns of cooperative thrift and credit society (CTCS) members in Ijebu-North Local Government Area of Ogun state. Data were collected through a well-structured questionnaire administered on CTCS members using multi-stage sampling techniques. Both descriptive and inferential statistics were used to achieve the research objectives . The results showed that more than half (58.3%) of cooperative members were females, with an average of 4 persons per households, and an average age of 36 years old with secondary level of formal education. The findings indicated that majority (..%) of CTCS had 21 membership strength with an average of 13 years existence. Results on mode and savings patterns revealed that monthly savings (53.3%) ranked 1st followed by quarterly savings while half-year savings were ranked least. F-statistic 12.741 confirms appropriateness of the overall regression equation at 1% level of significant. The adjusted R² estimated at 0.78 revealed that 78% of the variation in saving pattern of CTCS members was explained by the explanatory variables. Amount of loan collected, age of establishment of cooperative, number of loans application and number of loans granted significantly determined the CTCS members’ saving pattern. Policy implication is for CTCS members to get involved in regular savings monthly and be better equipped to manage their finances effectively.